Pengaruh Konsentrasi Kapang dan Lama Waktu Fermentasi terhadap Kadar Bioetanol dari Limbah Kulit Singkong (Manihot esculenta) - Setyawan Jati, Sasani; Widayatno, Tri (Jurnal Teknik Kimia USU, 2022)
The purpose of this research is the manufacture of bioethanol by utilizing cassava peel, this process is through acid hydrolysis and fermentation processes. Making bioethanol with variations in the effect of the rate of fermentation time (5th days and 10th days), as well as with variations in the amount of mold concentrations (10%, 20%, and 30%). The mold used is Saccharomyces cerevisiae, then the mixed bioethanol is separated through the distillation process and will produce bioethanol. Based on the data obtained, the highest ethanol content was found in the variation of the addition of 30% mold on the 5th day of 8.09% and the lowest ethanol content was found in the variation of the addition of 10% mold on the 10th days of 5.86%. This proves that each variation has an optimum value in producing bioethanol content from cassava peels.